Penerapan Model Pembelajaran Berbasis Masalah Sebagai Upaya Penguatan Karakter Demokratis Mahasiswa - Harahap, Rizky Dinda Sarmita; Murdiono, Mukhamad; Siagian, Liber (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the implementation of problem-based learning models in strengthening the democratic character of students. The type of research used in this study was descriptive research with a qualitative approach. The researchers used observation, interview, and documentation techniques to obtain data. In addition, they checked the validity of the data by triangulation technique. The data analysis techniques contained data reduction, data presentation, and verification. The results of this study indicated that the application of the problem-based learning model could strengthen the democratic character of students by orienting students to problems, organizing students for learning, guiding individual and group investigations, developing and presenting work, and analyzing and evaluating problem-solving processes. Furthermore, strengthening democratic character through problem-based learning is carried out when identifying issues that occur by integrating honest, fair, and participatory attitudes.